AB0541 The Prognostic Significance of The Birmingham Vasculitis Activity Score (BVAS) in Patients with Systemic Vasculitis Transferred To The Intensive Care Unit (ICU). (15th July 2016) - Biscetti, F.; Carbonella, A.; Parisi, F.; Cianci, F.; Bosello, S.L.; Tolusso, B.; Gremese, E.; Ferraccioli, G.
Abstract : Background: Systemic vasculitides represent a heterogeneous group of diseases that share clinical features including respiratory distress, renal dysfunction, and neurologic disorders. These diseases may often cause life-threatening complications requiring admission to an intensive care unit (ICU) [1]. Birmingham Vasculitis Activity Score (BVAS) is the most widely used generic tool to quantify disease activity in systemic vasculitis. Acute Physiology And Chronic Health Evaluation (APACHE II) is a simple and accurate assessment scale of the severity of disease in critically ill patients newly admitted to ICU. Objectives: The aim of this study was to identify possible prognostic biomarkers for patients with vasculitis admitted to ICU. Methods: A retrospective study was carried out from 2004 to 2014 in patients with systemic vasculitis admitted to the Rheumatology division and transferred to ICU due to clinical worsening, with a length of stay beyond 24 hours. An additional group of patients admitted to ICU, and without history of systemic vasculitis, were used as a matched-control group. A total of 25 patients were included in the analysis. Results: ICU mortality was significantly associated with higher BVAS scores performed in the ward (p<0.01) and at the admission in ICU (p=0.01), regardless of the value of APACHE II scores (p=0.50). We used receiver-operator characteristic (ROC) curve analysis to evaluate the possible cutoff value for the BVAS in the ward and in ICU and we found that a BVAS >8 in the ward and that a BVAS >10 in ICU were significantly related to the mortality in ICU (p<0.01). Conclusions: BVAS appears to be an excellent tool for assessing ICU mortality risk of patients with systemic vasculitides admitted to specialty departments. Our experience has shown that performing the assessment at admission to the ward is more important than determining the evaluation before the clinical aggravation causing the transfer to ICU. References: Befort P, et al. BMC Anesthesiol. 2013 Oct 1;13(1):27 Disclosure of Interest: None declared